National program of solidarity assistance Pension 65 and welfare social of beneficiaries in the districts of Puno and Chucuito - Tintaya-Duran, Humberto; Sullca-Cáceres , Richard (Revista revoluciones, 2019)
The research analyzes the relationship between the lines of intervention of the National Solidarity Assistance Program Pensión 65 and the social welfare of the beneficiaries in the districts of Puno and Chucuito. A quantitative, non-experimental, descriptive and correlational study was carried out. The research interest is focused on analyzing the relationship between economic subsidy, access to public services and the intervention of productive knowledge with the social well-being of the elderly. These dimensions were analyzed through the use of the surveys and for the analysis of results the statistical software SPSS was used; To assess the significance, the Chi-square test was used. Thanks to this, it was determined that the economic subsidy granted by the program does not have a significant relationship with the social welfare of the beneficiaries, as it is limited and mostly intended to cover food expenses. Access to public services is independent and does not have a significant relationship with social welfare, because most beneficiaries need medical attention because they have some type of illness and with a high weighting in the district of Chucuito they do not have access Timely to health services. Finally, it is concluded that there is a relationship between the intervention of productive knowledge and social welfare of the beneficiaries of the Pension 65 Program.
Keywords: Pension 65 Program; social welfare; productive knowledge; public services; economic subsidy